Role of the Shea Industry in the Socio-economic Lives of Women in the West Mamprusi District of Northern Ghana - WaduduAdamMohammed, Abdul-; Baah-Ennumh, Theresa Yaaba; RahimAbdulai, Abdul- (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
In Ghana, the shea trees grow in Upper East, Upper West and Northern Regions. The shea industry which is dominated by women has attracted the attention of researchers who investigated the value chain, the marketing and financing and the extent to which the tree can be domesticated in terms of plantation. This study examines the role of the shea in the lives of women. The research employed a case study approach to assess the role of shea in the social and economic lives of women in the study district. A purposive sampling technique was used where only women engaged in shea activities were interviewed. The women were divided into three strata namely shea pickers, shea marketers and shea processors to ensure a comparative assessment of the industrys contribution to these strata of women. Institutional data were also collected from relevant agencies. In all, 66 shea operators were interviewed in each of the three study shea communities. Thus an overall total number of 198 shea operators were interviewed in the West Mamprusi District in the Northern Region in addition to six relevant institutions. The study ascertained that the shea industry plays diverse roles in the lives of women. The industry contributes significantly to providing employment and income to the women. However, In terms of income, shea processors are found to obtain more income than shea pickers. The industry also contributes to the ability of women to meet their basic needs such as food, childrens educational needs and health. These notwithstanding, there is high illiteracy among the women, poor organization, lack of properly established institutional and regulatory structures, working in dangerous conditions, and most importantly depletion of shea trees. Based on the challenges, it is recommended that, credit and finance schemes should be instituted for women in the shea industry, women groups and cooperative formation should be encouraged, capabilities of women should be enhanced through training and equipments needed in the operation of the industry should be made available to women by NGOs and other relevant organisations.